Comparison between manufacturing sites shows differential adhesion, activation, and GPIbα expression of cryopreserved platelets. Issue 11 (12th October 2018) - Six, Katrijn R.; Delabie, Willem; Devreese, Katrien M.J.; Johnson, Lacey; Marks, Denese C.; Dumont, Larry J.; Compernolle, Veerle; Feys, Hendrik B.
Abstract : BACKGROUND: Transfusion of cryopreserved platelets (cryoplatelets) is not common but may replace standard liquid‐preserved platelets (PLTs) in specific circumstances. To better understand cryoplatelet function, frozen concentrates from different manufacturing sites were compared. STUDY DESIGN AND METHODS: Cryoplatelets from Denver, Colorado (DEN); Sydney, Australia (SYD); and Ghent, Belgium (GHE) were compared (n = 6). A paired noncryopreserved control was included in Ghent. Microfluidic‐flow chambers were used to study PLT adhesion and fibrin deposition in reconstituted blood. Receptor expression was measured by flow cytometry. Coagulation in static conditions was evaluated by rotational thromboelastometry (ROTEM). RESULTS: Regardless of the manufacturing site, adhesion of cryoplatelets under shear flow (1000/sec) was significantly (p < 0.05) reduced compared to control. Expression of GPIbα was decreased in a subpopulation of cryoplatelets comprising 45% ± 11% (DEN), 63% ± 9% (GHE), and 94% ± 6% (SYD). That subpopulation displayed increased annexin V binding and decreased integrin activation. PLT adhesion, agglutination, and aggregation were moreover decreased in proportion to that subpopulation. Fibrin deposition under shear flow was normal but initiated faster (546 ± 163 sec GHE) than control PLTs (631 ± 120 sec, p < 0.01), only in the absence of tissue factor. In static conditions, clotting time was faster, but clot firmness decreased compared to control. Coagulation was not different between manufacturing sites. CONCLUSION: Cryopreservation results in a subset of PLTs with enhanced GPIbα shedding, increased phosphatidylserine expression, reduced integrin response, and reduced adhesion to collagen in microfluidic models of hemostasis. The proportion of this phenotype is different between manufacturing sites. The clinical effects, if any, will need to be verified.